Production and characterization of alcoholic mango fermented from yeast strain isolated from commercial yeast (Research, Society and Development, 2022)
Fermented beverages of fruits are a viable and low-cost alternative to the utilization of fruits. The aim of the study was to produce and characterize a mango alcoholic fermented using Saccharomyces cerevisiae cells isolated from commercial yeast. The feedstock and fermentation process were characterized and the mango fermented showed: alcoholic content (7,61 ± 0,13 g.L-1), final sugar (1,24 ± 0,04 g.L-1), pH (3,73 ± 0,05), total acidity (83,34 ± 6,65 mEq.L-1), dry extract (96,75 ± 1,72 g.L-1), productivity by alcohol (0,23 ± 0,02 g.L-1. h-1), efficiency fermentation (91,50%), product to substrate conversion -Y p/s (0,470 g. g-1) and ethanol yield (85%). The total carotenoids and phenolics compounds contents were 17,33 ± 1,97 mg.100mL-1 and 24,60 ± 0,10 mg of catechin per milliliters, respectively. It is possible to produce a fermented mango alcoholic beverage of good quality and within the physical-chemical parameters required by legislation from S. cerevisiae yeast from commercial yeast.